The investigation on the NH reactivity of pentacoordinate spirophosphoranes by H/D exchange and NMR experiments. Issue 43 (24th October 2018) - Sun, Can; Cao, Shuxia; Zhao, Pei; Ma, Wenwen; Guo, Yanchun; Zhao, Yufen
Graphical abstract: Highlights: H/D exchange combined with NMR tracking experiments to explore structural property. Using proton-decoupled, proton-coupled 31 P NMR and 1 H NMR tracking experiments. Investigation on the steric hindrance and electronic effect of spirophosphoranes. The electronic effect was the biggest effect factor on the NH bond reactivity. Abstract: Different pentacoordinate spirophosphoranes were investigated by H/D exchange and NMR tracking experiments. The H/D exchanged site of spirophosphoranes was confirmed to be the NH bond instead of the PH bond according to the integration of the signal changes in proton-decoupled, proton-coupled 31 P NMR and 1 H NMR tracking experiments. The reactivity of NH bond at the spiroring of spirophosphoranes was explored by the rate constant of H/D exchange of different spirophosphoranes. The results demonstrated that the reactivity of NH bond of spirophosphoranes was influenced by steric hindrance and the species of substituent at phosphorus atom, and the electronic effect of the substituent was the main effect factor on the reactivity of the NH bond. The strong electron-withdrawing group at phosphorus resulted in more reactive NH bond of spirophosphoranes. These results are beneficial to further understand and explore the characteristics of pentacoordinate spirophosphoranes.